Contribution of cervical incompetence to occurrence of second trimester abortion in patients with polycystic ovary syndrome during the frozen embryo transfer cycle - Cheng, Tingting; Shi, Hao; Bu, Zhiqin; Yu, Yiping; Song, Wenyan; Haixia, Jin; Yao, Guidong (Frontiers in Endocrinology, 2024)
Background: Second-trimester abortion is a critical issue in infertile women with polycystic ovary syndrome (PCOS) treated with assisted reproductive technology (ART), cervical incompetence (CI) may play a role. Although previous studies have revealed an association between PCOS and CI in women undergoing ART with fresh embryo transfer, the associated risk factors in frozen embryo transfer cycles are still unknown. The primary objective of this study is to examine the impact of CI on the occurrence of second-trimester abortion in women with PCOS undergoing frozen embryo transfer. Methods: This retrospective cohort study included patients who underwent frozen-thawed embryo transfer and experienced second-trimester abortion between January 2012 and January 2020 from the Reproductive Medical Center of the First Affiliated Hospital of Zhengzhou University. Logit-transformed propensity score matching (PSM) was used to assess covariates. Patients were classified into the PCOS and non-PCOS groups. The PCOS group was further divided into two subgroups: the CI group and non-CI group. Results: After case matching with PSM, 278 patients were included: 139 each in the PCOS group and non-PCOS groups. More miscarriages were attributed to CI in the PCOS group compared with the control group (20.14% vs. 10.07%). Subsequently, in the PCOS group, CI and non-CI subgroup analyses revealed a higher transfer cleavage-stage embryo incidence in the CI group than in the blastocysts group (p=0.001). Moreover, the between-group miscarriage-related gestational age varied significantly (p=0.039). Binary logistic regression analysis revealed that cleavage embryo transfer (p= 0.047) was associated with increased CI risk in the PCOS group, besides, increasing the number of transferred embryos did not impact the occurrence of CI in patients with PCOS. Conclusion: CI independently predicted a higher risk of second-trimester abortion in patients with PCOS during the frozen embryo transfer cycle. What’s more, increasing the number of transferred embryos did not affect the incidence of CI in the PCOS group.